The impact of oral conditions on the quality of life of the Malaysian adult population: preliminary results - Saub, Roslan; Locker, D. (Malaysian Medical Association, 2006)
The aim of this paper is to describe the impact of oral conditions on the quality of life of the adult population of Malaysia. The adapted Malaysian Oral Health Impact Profile (L-OHIP-M) questionnaire was used. A total of two hundred and twenty respondents completed the L-OHIP (M). Overall, slightly more than 50 of the sample had at least one impact reported as either "very often" or "often". The younger age group, Indian ethnic and those who had tertiary education reported more impacts. The preliminary results revealed that a substantial proportion of the sample included in this study experienced frequent psychosocial impacts associated with oral conditions.